Roofs functions in vernacular residential buildings: case study in Kashan, Iran - Elham, Maghsoudi Nia; Abd Rahman, Nordin; Mohd Yunus, Mohd Yazid (ArchNet-IJAR: International Journal of Architectural Research, 2014)
The vernacular roofs in Iran served more than protective functions and were in response to the people’s behaviors. The case study has explored the different functions of the vernacular roofs regarding the people’s behaviors. It has focused on Kashan, as an ancient and historical city with hot and dry climate. The semi-structured interview has been conducted among the local master builders and experts, which respondents have answered to the open-ended questions. As the results show climate, religion, culture and economy affected people’s behaviors on the roofs and caused creating spatial, socio-cultural, spiritual, economic, recreational and passage functions of the roofs. In response to these functions, particular roofing strategies emerged, including aligned and connected roof, flat and double surface roof, staircase, partition walls around the roof, and some spaces on the roofs. Consequently, the vernacular roofs were in response to the people’s behaviors, improved physical and mental health, offered spiritual and intangible benefits. The study recommends professionals consider the people’s demands and behaviors during roofing in order to use all the potential of the roofs in residential buildings.